Examination of orthopedic and athletic injuries - Starkey, C.; Brown, S. D.; Ryan, J. (F. A. Davis Company, 2010)
The 3rd Edition of this popular work has been completely revised and updated to bring you all of the field's most current knowledge in an even easier-to-use new design. Its superb combination of detailed illustrations and precise language make even the most complicated concepts and techniques clear. Organized by body region, each chapter begins with a review of anatomy and biomechanics; proceeds through clinical evaluation, pathologies and related special tests; and concludes with a discussion of on-field or initial management of specific injuries. The text conforms to or exceeds the Athletic Training Educational Competencies. Distinctive boxes for each type of test, including goniometry, resisted range of motion and manual muscle tests, clinical tests, and special tests, are well-illustrated with photographs and line drawings. Evaluative Findings boxes summarize clinical findings for specific injuries or conditions. Observational Findings boxes help students to identify specific conditions or injuries.